The Role of the Western Australian Mining and Petroleum Research Institute with Particular Reference to Research and Development in Mining Engineering (The Australasian Institute of Mining and Metallurgy, 1984)
The Western Australian Mining and Petroleum Research Institute (WAMPRI) was established in 1981 by the Western Australian Government as a funding and co-ordinating Institute to foster research into the mining and petroleum industry within this State. To June 1984, the Institute has sponsored 34 projects with a total notional value of $2.5 million and an actual cash commitment of $1.5 million. Strong support for WAMPRI has come from Industry with 60 companies contributing half the money needed for the research grants.The 34 WAMPRI projects funded so far cover all aspects of the mining and petroleum geosciences.Several WAMPRI projects are concerned with gold including processing technology and the development of exploration models and techniques, they are providing successful results.Although well supported by Industry there is a surprising lack of applications being submitted to the Institute in the area of mining engineering, where it is felt there is much scope for research projects.